Importance of secondary damage in downer cows. Issue 5 (May 2016) - Poulton, PJ; Vizard, AL; Anderson, GA; Pyman, MF
Abstract : Objective: To investigate the relative importance in downer cows of the primary cause of recumbency in comparison with secondary complications. Methods: Downer dairy cows were monitored during their recumbency under field conditions in South Gippsland, Victoria, Australia. The cause of the original recumbency of the 218 cows was determined and secondary damage, status on day 7 and final outcome were recorded. Results: Some type of secondary damage was found in 183/218 (84%) cows, of which 173/218 (79%) had damage deemed to be clinically important. By day 7, 52 (24%) had recovered and 69 (32%) eventually recovered. Of the 149 (68%) cows that were euthanased or died, 23 (15%) were deemed to have been lost solely from the primary cause, 107 (72%) from secondary damage and 19 (13%) from a combination of both. Conclusion: There was no difference in recovery among the five broad groups of causes of primary recumbency. Secondary damage was very common and presented in a large variety of ways, with many cows having multiple types of secondary damage concurrently. For most cows the secondary damage was more important than the initial primary damage in determining their fate.